Leader's coaching for improving ESL teacher practice at a secondary school in Sabah: An investigation / Dyna Nurliyana Mohamad Yusof - Mohamad Yusof, Dyna Nurliyana (2014)
The adoption of external coaches to enhance English teachers’ teaching practices in Malaysian school is worrying. Empirical studies showed that external coaches unable to sustain changes in long run. This research aims are to identify the possibility of coaching by the Principal from a secondary school in Sabah to influence the teaching and learning process of English language for teachers apart from to identify the elements leaders would need to increase knowledge by facilitating the exploration of needs, motivations, and skills to assist English language teachers in making evident changes, and identify the influences of leadership-based coaching for constant proactive learning-teaching process on the English language teachers’ practices. This research is based on mixed-method approach obtained from semi structured interview, open-ended questions and survey questionnaire. The population were mainly at secondary school principal and English teachers in one urban school. The data was analysed to evaluate and determine the coaching adopted by Principal able to influence English teachers teaching practices. The research suggested that not only the English teaching practices of the teachers in the school organization exceedingly improve, it also gave variety to English teaching techniques and most importantly the English teachers’ professional development was enhanced under the school Principal’s coaching. Hopefully, that this study can benefit all stakeholders involved in this issue, particularly teachers, students and the Ministry of Education (MOE).